A new class of hepatitis B and D virus entry inhibitors, proanthocyanidin and its analogs, that directly act on the viral large surface proteins. Issue 4 (17th January 2017) - Tsukuda, Senko; Watashi, Koichi; Hojima, Taichi; Isogawa, Masanori; Iwamoto, Masashi; Omagari, Katsumi; Suzuki, Ryosuke; Aizaki, Hideki; Kojima, Soichi; Sugiyama, Masaya; Saito, Akiko; Tanaka, Yasuhito; et al.
Abstract : Introduction of direct‐acting antivirals against hepatitis C virus (HCV) has provided a revolutionary improvement in the treatment outcome. In contrast to HCV, however, the strategy for developing new antiviral agents against hepatitis B virus (HBV), especially viral‐targeting compounds, is limited because HBV requires only four viral genes for its efficient replication/infection. Here, we identify an oligomeric flavonoid, proanthocyanidin (PAC) and its analogs, which inhibit HBV entry into host cells by targeting the HBV large surface protein (LHBs). Through cell‐based chemical screening, PAC was identified to inhibit HBV infection with little cytotoxic effect. PAC prevented the attachment of the preS1 region in the LHBs to its cellular receptor, sodium taurocholate cotransporting polypeptide (NTCP). PAC was shown to target HBV particles and impair their infectivity, whereas it did not affect the NTCP‐mediated bile acid transport activity. Chemical biological techniques demonstrated that PAC directly interacted with the region essential for receptor binding in the preS1 region in the LHBs protein. Importantly, PAC had a pan‐genotypic anti‐HBV activity and was also effective against a clinically relevant nucleoside analog‐resistant HBV isolate. We further showed that PAC augmented the ability of a nucleoside analog, tenofovir, to interrupt HBV spread over time in primary human hepatocytes by cotreatment. Moreover, derivative analysis could identify small molecules that demonstrated more‐potent anti‐HBV activity over PAC. Conclusion : PAC and its analogs represent a new class of anti‐HBV agents that directly target the preS1 region of the HBV large surface protein. These agents could contribute to the development of a potent, well‐tolerated, and broadly active inhibitor of HBV infection. (Hepatology 2017;65:1104‐1116).